Better endovascular mechanical thrombectomy outcome in atrial fibrillation patients with acute ischemic stroke: A single-center experience. Issue 8 (8th July 2020) - Lin, Chun-Jen; Luo, Chao-Bao; Chien, Chun; Chang, Feng-Chi; Lin, Chung-Jung; Lee, I-Hui; Hsu, Li-Chi; Chung, Chih-Ping; Liu, Hung-Yu; Chi, Nai-Fang; How, Chorng-Kuang; Wang, Shuu-Jiun; et al.
Abstract : Background: Endovascular thrombectomy (EVT) has become the standard treatment for acute ischemic stroke with large vessel occlusion. Atrial fibrillation (AF) is one of the major causes. However, the impact of AF on the treatment has not yet been clearly discussed. This study is to evaluate the influence of AF on the outcomes of EVT in patients with acute ischemic stroke. Methods: Data from our Stroke Registry Database from April 2015 to July 2018 were reviewed. Technical efficacy, functional, and safety outcomes were reported and compared between patients with and without AF. A multivariate logistic regression model was performed to identify the predictors of the good functional outcome. Results: We reviewed 83 eligible patients receiving EVT. Patients (51.8%) were eventually found to have AF. The substantial reperfusion rate (modified thrombolysis in cerebral infarction 2b-3) was 72.1% and 55.0% in patients with and without AF, respectively, inclusive of a learning curve ( p = 0.12). The good functional outcome (90-day modified Rankin scale: 0 to 2) rate was 55.8% and 17.5% in patients with and without AF, respectively ( p < 0.01). A multivariable logistic regression analysis showed that age <70 years, the substantial reperfusion, and the presence of AF were three significant predictors for a good functional outcome. Conclusion: Our study showed that patients with AF responded significantly better to EVT than those without AF did. Intracranial atherosclerotic diseases in patients without AF which were especially refractory to EVT may contribute to the difference of the functional outcomes between the two groups.